Muscle-Strengthening Exercise Questionnaire (MSEQ): an assessment of concurrent validity and test–retest reliability. Issue 1 (14th February 2022) - Shakespear-Druery, Jane; De Cocker, Katrien; Biddle, Stuart J H; Bennie, Jason
Abstract : Objectives: Muscle-strengthening exercise (MSE) has multiple independent health benefits and is a component of global physical activity guidelines. However, the assessment of MSE in health surveillance is often limited to the constructs of frequency (days/week), with little focus on constructs such as MSE type, muscle groups targeted and intensity. This study describes the test–retest reliability and concurrent validity of the Muscle-Strengthening Exercise Questionnaire (MSEQ), which was developed to assess multiple MSE participation constructs. Methods: The MSEQ was developed to assess the weekly frequency, session duration and intensity, types of MSE (eg, weight machines, bodyweight exercise) and muscle groups targeted. Two convenience samples of adult participants were recruited. Test–retest reliability was completed online by 85 participants. Concurrent validity was assessed for 54 participants using an online 7-day MSE log. Results: The MSEQ shows high test–retest reliability for frequency, duration and level of intensity for each of the four MSE types (using weight machines, bodyweight exercises, resistance exercises and holistic exercises), and for the four types combined (ρ range 0.76–0.91). For muscle groups targeted, the reliability ranged mostly from moderate-to-substantial for each of the four MSE types (κ range 0.44–0.78) and fair-to-moderate for the four types combined (κ range 0.35–0.51). Concurrent validity for frequency, duration and level of intensity for each of the four MSE types, and the four types combined, was moderate-to-high (ρ range 0.30–0.77). Conclusion: The MSEQ shows acceptable reliability and validity for four key MSE constructs. This new MSEQ survey instrument could be used to assess adults' MSE.